Pengaruh Health Education terhadap Tingkat Pengetahuan Remaja tentang Bahaya Seks Bebas di SMAN 1 Krueng Barona Jaya Aceh Besar - Maulidarni Maulidarni; Syukriadi Syukriadi; Nurul Amna (Jurnal Rumpun Ilmu Kesehatan, 2025)
Adolescence is an important period in which individuals experience various dynamics of change, both psychologically and biologically. In general, biological changes in this age group occur more rapidly than mental development. This phenomenon has contributed to the emergence of various problems, one of which is promiscuous behavior, which Indonesia is currently facing. The research conducted at SMAN 1 Krueng Barona Jaya aimed to analyze how health education can contribute to increasing adolescents' knowledge about the risks of promiscuity. This study was conducted on May 14, 2025, with a pre-experimental research design, using a One Group Pre-test Post-test design. A total of 44 students were selected as respondents through proportional sampling. The main measurement tool was a knowledge questionnaire used as a data collection instrument, while statistical analysis was performed using the Wilcoxon Sign Rank Test. The pretest findings showed that 8 students (18.2%) were in the low knowledge category, 7 students (15.9%) were in the moderate knowledge category, and 29 students (65.9%) had good knowledge. In the post-test stage, there was a significant increase with 39 respondents (88.6%) in the good knowledge category and 5 respondents (11.4%) in the sufficient category. Health education was proven to have a significant impact on adolescents' knowledge about the dangers of promiscuity, as indicated by a p-value of 0.001. Through these findings, it is hoped that adolescents can be more proactive and responsible in obtaining accurate information about reproductive health, especially regarding the dangers of promiscuous behavior.